Elements pollution and ecological risk assessment of coastal sediments along the Nile Delta - Mohamed A. Hassaan; Amr G. Dardeer; Ahmed El Nemr (Scientific Reports)
Abstract The Nile Delta coastal area surface sediments were evaluated for twenty-five elements. Inductively coupled plasma-mass spectroscopy (ICP-MS method) was used to analyze the digested solutions, previously filtered using discrete 0.2 μm PTFE syringe filters according to USEPA protocols. Potentially toxic elements (PTEs) and pollution levels were estimated using several indices. Pollution guides such as the enrichment factor (EF), contamination degree (C d), geoaccumulation index (I geo), and pollution load index (PLI) are mainly determined by actually toxic elements such as Cr, Co, Cd, Hg and Pb, while Principal component analysis (PCA), concerned with the distribution of all elements in sediment to determine the sources of elements. The following is the order of the EF values: Mn < Cu < Zn < Ni < Pb < Cr. The areas under investigation showed no pollution with Cr, Cu, Mn, Ni, Pb, or Zn, as indicated by their (I geo ≤0) values and C d (< 1.5). Significant connections between Mn, Fe, Cr, Co, and Ni values were observed, indicating comparable origins. In the current study, the children’s Hazard Quotient (HQ) results for the dermal exposure pathway are low, but adult values are 3–4 times higher. The chronic daily intake (CDI Dermal) and carcinogenic risk (CR Dermal) through dermal absorption were also investigated.